ASPEK HUKUM PENCEGAHAN DAN PENANGGULANGAN KORUPSI MELALUI PENDIDIKAN ANTIKORUPSI DI PERGURUAN TINGGI KHUSUSNYA DI UNIVERSITAS NEGERI JAKARTA - Martini Martini; Efridani Lubis (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2015)
Although Indonesia has long history fighting corruption since its independence, however the fighting has not given positive resulted yet. The corruption cases is increasing from one rezim to another, even after reformation era which put its based movement toward fighting corruption. This phenomena drive many Indonesian people, experts, and scholars to evaluate the essence of fighting such bad behaviour either from culture, legal, and education perspective. Scholars suggested that the effective way of fighting the corruption is in preventive scheme rather in represive one. In this sense, it is education that could give great impact to build anti corruption character. The challenge in formulating such system in higher education not only due to the material or the subject given to the students, but also the method that need different approach to make sure that the needed character has been developed well.